2022
DOI: 10.29040/jie.v6i2.4998
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Firm Size Dan Aktivitas Perusahaan Terhadap Pengungkapan Sustainability Report

Abstract: The purpose of this study is to look at the effect of profitability, firm size, and company activities on disclosure of sustainability reports. The measurement index used as a reference for the sustainability report in this study is the Global Reporting Initiative (GRI) G4. The population in this study is non-financial sector companies listed on the Indonesia Stock Exchange in 2016-2019. The sample companies in this study were selected based on a purposive sampling method with several criteria to obtain 10 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Tingkat profitabilitas perusahaan yang semakin tinggi, maka akan semakin tinggi juga pengungkapan sustainability report yang dilakukan oleh perusahaan (Putra et al, 2023). Sedangkan menurut Damayanty et al (2022), profitabilitas memiliki pengaruh negatif secara signifikan terhadap pengungkapan sustainability report. Hal ini disebabkan karena perusahaan dengan profitabilitas yang tinggi cenderung tidak melaporkan hal selain kesuksesan kinerja keuangan.…”
Section: Pembahasan Pengaruh Profitabilitas Terhadap Pengungkapan Sus...unclassified
“…Tingkat profitabilitas perusahaan yang semakin tinggi, maka akan semakin tinggi juga pengungkapan sustainability report yang dilakukan oleh perusahaan (Putra et al, 2023). Sedangkan menurut Damayanty et al (2022), profitabilitas memiliki pengaruh negatif secara signifikan terhadap pengungkapan sustainability report. Hal ini disebabkan karena perusahaan dengan profitabilitas yang tinggi cenderung tidak melaporkan hal selain kesuksesan kinerja keuangan.…”
Section: Pembahasan Pengaruh Profitabilitas Terhadap Pengungkapan Sus...unclassified
“…Company size describes the large and small scale of the company. Increasing a company's size will result in a larger nominal asset, an increase in sales, having a credible information system and having better position stakeholders (Damayanty, Wahab, et al, 2022). The stability of the company will be better calculated, then the resulting estimation errors will reflect that it is smaller than that of a large company.…”
Section: Introductionmentioning
confidence: 99%
“…(Dewi dan Sari, 2019;Kumar et al, 2021;Liana, 2019;Rahman dan Alsayegh, 2021) in their study found that profitability has a positive and significant effect on the disclosure of sustainability reports. Meanwhile, research results (Bhatia dan Tuli, 2017;Damayanty et al, 2022) state that profitability has a negative and significant effect. However (Madani dan Gayatri, 2021;Setiawan et al, 2019;Wahyuningrum et al, 2022) found that profitability has no significant effect on the disclosure of sustainability reports.…”
Section: Introductionmentioning
confidence: 99%